Balanced Scorecard Analysis in Corporate Strategic Decision Making - Dewantara, Yuni Putri (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Decision making is an important aspect in the company. Strategic management is strategic decision making, which enables the company to adapt to the external environment and influences the function and direction of the company's development. Companies need appropriate measurement methods to measure the effectiveness of activities, as well as the success of implementing strategies and results in accordance with company objectives, namely the balanced scorecard (BSC). This research aims to obtain analysis related to the use of BSC in strategic decision making. This research uses a literature review method of 52 related articles and books. In accordance with the context of strategic management, companies that apply BSC can increase the achievement of strategic goals and improve their performance. BSC is able to support and facilitate strategic decision making because of its comprehensive company situation analysis capabilities which make it easier for managers to carry out structured and broad analysis to achieve goals and results by focusing on what is important. Managers are focused in making decisions. BSC is a good strategic management tool to be implemented in a company. BSC helps companies to achieve their strategic goals. BSC relies on financial and non-financial aspects. BSC provides a comprehensive picture for companies to take the right strategic decisions and steps for the company's survival. Future research can examine more deeply the use of BSC in large and smaller scale companies such as MSMEs.